DEFINITION OF THE DISTORTED MENTALITY OR PSYCHOLOGY OF WOMEN IN THE STORIES OF NASIRA SHARMA - P. Jayashree; L. Tillai Selvi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
There has been a lot of change in the status of women in independent India. Nowadays women are progressing in the field of politics, society, economy, culture, science and education. Women played an important role in the freedom struggle. After independence, women came out of the house and contributed to the development of the country. Changes in the status of women after independence: • Women are no longer confined to the four walls of the house. • The main purpose of women's work is to earn money and use time properly. • Women are developing mentally and physically. • Women are also gaining equal rights with men in the economic field.